2016
DOI: 10.1007/s00415-016-8144-x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of relapses in primary progressive multiple sclerosis after fingolimod withdrawal

Abstract: We report two cases of primary progressive multiple sclerosis (PPMS) included in the INFORMS cohort, experiencing a relapse related to a single MRI gadolinium-enhancing lesion 3 months after fingolimod withdrawal. These two patients share similarities with relapsing-remitting multiple sclerosis cases described in the same situation, suggesting that the initiating process of the active demyelinating plaques is also present in PPMS, even without relapses, but may be triggered as fingolimod is withdrawn. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…Two previously reported patients6 share similarities with our case. They both had PPMS, participated in INFORMS, and developed relapses and MRI‐documented disease activity 3–6 months after treatment cessation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Two previously reported patients6 share similarities with our case. They both had PPMS, participated in INFORMS, and developed relapses and MRI‐documented disease activity 3–6 months after treatment cessation.…”
Section: Discussionsupporting
confidence: 89%
“…Irrespective of the disease course, withdrawal of DMT in MS poses the risk of resuming disease activity including rebound 3, 6, 7. Whilst progressive MS, particularly PPMS is often characterized by a relative quiescence in terms of lesion activity detected on MRI,8 there are many exceptions from this rule, and PPMS should therefore be considered as one end of the spectrum of MS presentations (the other being relapsing MS with a high relapse rate), rather than an altogether distinct subtype 8.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, in more advanced PPMS, relapses and focal MRI activity were observed after the discontinuation of DMTs. 19,20 Overall, these observations concur with pathology studies showing, both in SPMS and PPMS cases, similar degrees of inflammatory infiltrates, axonal loss, and cortical demyelination, thus supporting the notion of MS being a single-stage disorder. [21][22][23][24] This is in line with epidemiological observations of a unified disease model, where PPMS and SPMS patients manifest clinical progression at similar mean ages and experience a similar rate of disability accumulation.…”
Section: Pathologysupporting
confidence: 83%
“…Most searches covered a period of up to February 2017, no signals of abuse, misuse, diversion, dependence or withdrawal with fingolimod were identified." Several cases of potential rebound or relapse of MS symptoms following discontinuation of fingolimod (Alroughani et al 2014;Alvarez-Gonzalez et al 2017;Beran et al 2013;Berger et al 2015;Czlonkowska et al 2017;Davion et al 2016;Faissner et al 2015;Forci et al 2017;Fragoso et al 2019;Ghezzi et al 2013;Giordana et al 2018;Gunduz et al 2017;Hakiki et al 2012;Havla et al 2012;La Mantia et al 2014;Lapierre et al 2016;Lapucci et al 2019;Novi et al 2017;Sacco et al 2020;Sanchez et al 2018;Sempere et al 2013;Ward et al 2016) and one potential case from a clinical trial involving siponimod (Litwin et al 2018) were reported. In the latter case, disease exacerbation was reported 12 weeks after siponimod discontinuation.…”
Section: Post-market Reports Of Actual Abuse Misuse Dependence or Withdrawalmentioning
confidence: 99%
“…In addition, the FDA review documents for siponimod (Center for Drug Evaluation and Research (CDER), 2019b ) indicate that “The Sponsor conducted searches for reports of abuse-related signals with fingolimod (Gilenya®) using publicly available post-marketing sources, including World Health Organization (WHO) VigiBase, FDA Adverse Event Reporting System (FAERS), National Poison Data System (NPDS), Drug Abuse Warning Network (DAWN, for the year 2011), scientific literature (Pubmed, up to January 2018), and Internet forums (Erowid Experience Vaults, Bluelight, and Drug Form; up to January 2018). Most searches covered a period of up to February 2017, no signals of abuse, misuse, diversion, dependence or withdrawal with fingolimod were identified.” Several cases of potential rebound or relapse of MS symptoms following discontinuation of fingolimod (Alroughani et al 2014 ; Alvarez-Gonzalez et al 2017 ; Beran et al 2013 ; Berger et al 2015 ; Czlonkowska et al 2017 ; Davion et al 2016 ; Faissner et al 2015 ; Forci et al 2017 ; Fragoso et al 2019 ; Ghezzi et al 2013 ; Giordana et al 2018 ; Gunduz et al 2017 ; Hakiki et al 2012 ; Havla et al 2012 ; La Mantia et al 2014 ; Lapierre et al 2016 ; Lapucci et al 2019 ; Novi et al 2017 ; Sacco et al 2020 ; Sanchez et al 2018 ; Sempere et al 2013 ; Ward et al 2016 ) and one potential case from a clinical trial involving siponimod (Litwin et al 2018 ) were reported. In the latter case, disease exacerbation was reported 12 weeks after siponimod discontinuation.…”
Section: Post-market Reports Of Actual Abuse Misuse Dependence or Withdrawalmentioning
confidence: 99%